2019
DOI: 10.15244/pjoes/90791
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Effluents Harbor a Unique Diversity of Fungal Community Structures as Revealed by High-throughput Sequencing Analysis

Abstract: The actual extent of fungal diversity in different environmental media is still a subject of ongoing research. Little is currently known about the diversity of fungal populations in industrial streams. This study characterized the fungal diversity of different industrial effluents using a high-throughput sequencing approach. A total of 234617 quality filtered reads were obtained from the collected wastewater samples. Phylogenetic taxonomy revealed that resident fungal communities were classified as 6 phyla, 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…(P3-01), and Trichoderma viride (P1-01). Several studies [16][17][18] show that filamentous fungi from the phylum Ascomycota are common in mycoflora in industrial effluents. The growth capacity of fungal strains at different chromium (VI) concentrations was evaluated in solid medium ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…(P3-01), and Trichoderma viride (P1-01). Several studies [16][17][18] show that filamentous fungi from the phylum Ascomycota are common in mycoflora in industrial effluents. The growth capacity of fungal strains at different chromium (VI) concentrations was evaluated in solid medium ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…All PCR products were sequenced using the Illumina Mi-Seq platform at Inqaba Biotechnology (Pretoria, South Africa). Mothur (V 1.39.5) pipeline was used to Analyse the raw sequence data following previous methods 74,75 . Briefly, reads with more than 1% ambiguities or 8% of homopolymers were excluded from processing after merging the paired-end reads into contigs .…”
Section: Methodsmentioning
confidence: 99%
“…Our results support and corroborate the findings of Pietryczuk et al [ 19 ] who revealed that water pollution usually leads to a decrease in the taxonomic diversity of aquatic hyphomycetes, including the complete disappearance of some species such as Tetracladium breve or Tricladium sp. Similarly, Selvarajan et al [ 48 ] reported lower fungal diversity and species richness in highly contaminated environments.
Fig.
…”
Section: Methodsmentioning
confidence: 96%